Theological Diversity in the Letters of St. Paul - Drane, J. W. (Tyndale bulletin, 1976)
Diversity between realised and apocalyptic eschatology in Paul’s letters provides evidence that Paul's thought did not develop in any formal way; both perspectives are clearly visible from the outset.